Persepsi Konsumen terhadap Buah Jeruk Lokal dan Jeruk Impor di Kota Denpasar - MONICA INDAH LESTARI SIMARMATA; I MADE SUDARMA; IGAA LIES ANGGRENI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Consumer Perception of Local and Imported Orange in Denpasar The purpose of this study was to determine the level of consumer perceptions of localcitrus fruits and imported oranges in Denpasar City and to find out whether there weredifferences in consumer perceptions of local citrus fruits and imported oranges inDenpasar City. This research was conducted in Denpasar City, namely in the traditionalmarkets and modern markets that have been determined. The population in this studywere consumers who bought and consumed local citrus fruits and imported oranges usingthe accidental sampling method, which was accidentally taking samples at the researchlocation while buying or having consumed local citrus fruits and imported oranges, thenumber of respondents was 40. Data collection was used in This study uses interviewmethods, namely structured interviews and in-depth interviews. The data analysis used inthis study is descriptive analysis and Mann-Whitney test analysis (U Test) using SPSS20.Oranges are one of the most consumed fruits by the community, because besides beingeasily accessible to oranges, they also have high vitamin C content. The people ofDenpasar City are one of the consumers who buy and consume local citrus fruits andimported oranges, because besides being consumed citrus fruit is used as acomplementary means of religious ceremonies for Hindus on holidays. Various types oforanges sold on the market make consumers have to make decisions about the type oforanges that will be bought. The level of consumer perceptions of imported oranges ishigher than the level of consumer perception of local oranges. Indicators of taste, color,texture, aroma, availability, and price determine the different perceptions of local jeurk and imported oranges in Denpasar City.Based on the results of analysis, consumers consider that the quality of imported orangesis better than local oranges. Researcher's suggestion is that there is a need for firmnessfrom the government regarding the holding of imported fruit restrictions so as not tosuppress similar products produced domestically.